1985
DOI: 10.3382/ps.0640093
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Products in Chicken Meat After Frozen Storage, Microwave and Convection Oven Cooking, Refrigerated Storage, and Reheating

Abstract: Oxidation products were measured in chicken breast and leg meat during a series of common household processing steps (frozen storage, microwave and convection cooking, refrigerated storage after cooking, and reheating). Malondialdehyde (MDA) in fat from meat was measured by an improved thiobarbituric acid (TBA) assay with antioxidant protection; and fluorescent products (FP) were measured in organic and aqueous layers from Folch-extracted meat samples by fluorescence spectrophotometry. Fat from breast meat con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…For our frozen samples, the fatty acid ethyl ester was microwaved or steam-heated immediately after being frozen. Our results show no differences in MA formation either between the fresh and frozen samples or between the two cooking methods, and the trends observed were similar to the results for either fresh or short-term frozen (3 months) samples reported by Pikul et al (1985).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For our frozen samples, the fatty acid ethyl ester was microwaved or steam-heated immediately after being frozen. Our results show no differences in MA formation either between the fresh and frozen samples or between the two cooking methods, and the trends observed were similar to the results for either fresh or short-term frozen (3 months) samples reported by Pikul et al (1985).…”
Section: Resultssupporting
confidence: 90%
“…Lipid peroxidation products formed from various foods under cooking conditions have been studied using the thiobarbituric acid (TEA) assay (Pikul et al, 1985). The TEA assay, however, is never specific to the product of interest (Namiki, 1990).…”
mentioning
confidence: 99%
“…Also using raw sardine, Castrillo n et al (1996a) presented the e †ect of freezing on the biological value of protein and the nutrients. Some research can be found in the literature concerning defrosting with conventional and microwave ovens and it has been shown that microwave heating produces less lipid deterioration than conventional heating (Pikul et al 1985 ;King and Bosch 1990 ;Salama 1993). However, no research has been reported on the e †ect of freezing followed by reheating has on precooked foods.…”
Section: Introductionmentioning
confidence: 99%
“…The wooden breast meat becomes more susceptible to this type of oxidation, which could result in meat with worse nutritional value due to the rancidity of fats ( Cecchi, 1999 ), since according to the findings in the literature, as well as the results obtained in the present experiment, the samples affected by wooden breast had higher levels of fat, a product of inflammatory processes ( Petracci et al, 2019 ). The difference between the levels of oxidation and the severity degrees increases during frozen storage, because there are several chemical reactions taking place, with factors that promote such oxidative reactions, which, in the case of birds, is the high presence of lipids ( Asghar and Bhatti, 1988 ) and storage time ( Pikul et al, 1985 ).…”
Section: Resultsmentioning
confidence: 99%